Self-Organised Schools Educational Leadership and Innovative Learning Environments - De Toni, Alberto F. (Routledge Advances in Management Learning and Education, 2023)
Self-Organised Schools: Educational Leadership and Innovative Learning Environments describes the results of the research we carried out at fourteen Italian schools that highlight how there is a positive correlation between the capabilities of school self-organization and the innovativeness of learning environments: in other words, the more self-organized schools are, the more innovative learning environments are. The results of this work are part of the strand of research of bottom-up emergency and self-organization, an extremely fruitful trend as shown by Sugata Mitra, the founder of the Self-Organized Learning Environments, according to whom, "education is a self-organized system where learning is an emerging phenomenon". This book gives new insights on self-organization studies, and most of all, to the idea that change - organizational and educational innovation - sparks from the bottom. This book is aimed specifically at school principals of all levels, scholastic reformers, educational scholars, organisation and management consultants who want to innovate learning and management of learning. These actors will benefit drawing useful examples from more than thirty different learning environments worldwide, fourteen examples of schools that self-organize, two frameworks - and two ready-to-use questionnaires - measuring the innovativeness of a learning environment, and the capability of a school to self-organize. Self-organization is the most fascinating future of innovative principals